Fenofibrate Decreases Ethanol-Induced Neuroinflammation and Oxidative Stress and Reduces Alcohol Relapse in Rats by a PPAR-α-Dependent Mechanism - Cristina Ibáñez; Tirso Acuña; María Elena Quintanilla; Diliana Pérez-Reytor; Paola Morales; Eduardo Karahanian (Antioxidants, 2023)
High ethanol consumption triggers neuroinflammation, implicated in sustaining chronic alcohol use. This inflammation boosts glutamate, prompting dopamine release in reward centers, driving prolonged drinking and relapse. Fibrate drugs, activating peroxisome proliferator-activated receptor alpha (PPAR-α), counteract neuroinflammation in other contexts, prompting investigation into their impact on ethanol-induced inflammation. Here, we studied, in UChB drinker rats, whether the administration of fenofibrate in the withdrawal stage after chronic ethanol consumption reduces voluntary intake when alcohol is offered again to the animals (relapse-type drinking). Furthermore, we determined if fenofibrate was able to decrease ethanol-induced neuroinflammation and oxidative stress in the brain. Animals treated with fenofibrate decreased alcohol consumption by 80% during post-abstinence relapse. Furthermore, fenofibrate decreased the expression of the proinflammatory cytokines tumor necrosis factor-alpha (TNF-α) and interleukins IL-1β and IL-6, and of an oxidative stress-induced gene (heme oxygenase-1), in the hippocampus, nucleus accumbens, and prefrontal cortex. Animals treated with fenofibrate showed an increase M2-type microglia (with anti-inflammatory proprieties) and a decrease in phagocytic microglia in the hippocampus. A PPAR-α antagonist (GW6471) abrogated the effects of fenofibrate, indicating that they are dependent on PPAR-α activation. These findings highlight the potential of fenofibrate, an FDA-approved dyslipidemia medication, as a supplementary approach to alleviating relapse severity in individuals with alcohol use disorder (AUD) during withdrawal.